Potential of Carotenoid from Freshwater Red Alga, Caloglossa beccarii DeToni on Color Enhancement in Harleguin Rasbosa(Trigonostigma espei) and Blue Danio (Davario regina) - Chankaew, Suriya; Wanna, Jiraporn; Penprapai, Pensri; Chankaew, Wanninee (Princess of Naradhiwas University Journal, 2019)
The objective of this study was to consider the effect of total carotenoid from freshwater red alga, Caloglossa beccarii Di Toni added in artificial feed on pigmentation, growth and survival rate of harleguin rasbosa (Trigonostigma espei) and blue danio (Davario regina). Five levels with three replication of total carotenoid; 0, 15, 30, 60 and 120 mg/kg were added in to the artificial feed. The color value, growth, survival rates was measured and the fish flesh, fin and scale were collected for carotenoid analysis after 8 weeks of feeding trial. The results found that both two species fed diet of all treatment had no significantly different (p>0.05) on growth and survival rate. The harleguin rasbosa was no significant differences (p>0.05) in pigmentation among treatment, while those significant differences (p<0.05) in blue danio. The addition of the carotenoid in artificial feed could improve the cumulative carotenoid content in flesh and fin of harleguin rasbosa, but could improve the skin pigmentation (yellow clolor) of blue danio. These suggested that the optimum of concentration of total carotenoid for both species color enhancer diets can be used at 30 mg/kg. This first information obtained will be useful in providing basic information about total carotenoid from C. beccarii and applying for aquaculture in the future.